Observations of 6.7 GHz methanol masers with East-Asian VLBI Network. I. VLBI images of the first epoch of observations. (1st May 2014) - Fujisawa, Kenta; Sugiyama, Koichiro; Motogi, Kazuhito; Hachisuka, Kazuya; Yonekura, Yoshinori; Sawada-Satoh, Satoko; Matsumoto, Naoko; Sorai, Kazuo; Momose, Munetake; Saito, Yu; Takaba, Hiroshi; Ogawa, Hideo; et al.
Abstract : Very-long-baseline interferometry (VLBI) monitoring of the 6.7 GHz methanol maser allows us to measure the internal proper motion of maser spots and therefore study the gas motion around high-mass young stellar objects. To this end, we have begun monitoring observations with the East-Asian VLBI Network. In this paper we present the results of the first epoch observation for 36 sources, including 35 VLBI images of the methanol maser. Since two independent sources were found in three images, images of 38 sources were obtained. In 34 sources, 10 or more spots were detected. The observed spatial scale of the maser distribution was from 9 to 4900 astronomical units, and the following morphological categories were observed: elliptical, arched, linear, paired, and complex. The position of the maser spot was determined with an accuracy of approximately 0.1 mas, which is sufficiently high to measure the internal proper motion from two years of monitoring observations. The VLBI observation, however, detected only approximately 20% of all maser emissions, suggesting that the remaining 80% of the total flux was spread into an undetectable extended distribution. Therefore, in addition to high-resolution observations, it is important to observe the whole structure of the maser emission including extended low-brightness structures, in order to reveal the associated site of the maser and gas motion.